Nutraceutical Enriched Vegetables: Molecular Approaches For Crop Improvement - SANJAY KUMAR RAI; NEHA ARORA; NEHA PANDEY; RAM PRASAD MEENA; KAVITA SHAH; SHASHI PANDEY-RAI (International Journal of Pharma and Bio Sciences, 2012)
Nutraceuticals have been explored recently as sustainable alternatives for the control and prevention of large number of diseases. They have received considerable attention because they are safe, efficacious and have potential nutritional value as well as therapeutic effects. Among natural dietary supplements, vegetables being low in calories are packed with vitamins, minerals, antioxidants and phytochemicals. They play an important part in the human diet and are a major source of biologically active nutraceuticals. Some popular phyto-nutraceuticals include lycopene from tomato, curcumin from turmeric, carotenoids from carrot etc. Majority of the vegetable originated nutraceuticals are claimed to possess multiple therapeutic benefits; though substantial evidence for their benefits as well as unwanted effects is lacking. The present review has been devoted towards better understanding of the phyto-nutraceuticals from different vegetables based on their disease specific indications and enhancing nutraceutical qualities of vegetables through biotechnological/molecular approaches.